A historical look at the development of the 17th street corridor through the Kansas State University campus - Suzuki, Tomoya (Kansas State University, 2010)
This report examines how 17th Street on the Kansas State University campus, initially a service road on the west edge of the campus, has become a major point of public campus access while retaining its function as a service road. In addition, this report conducts interviews with 10 persons with various backgrounds and experiences involving 17th Street to understand public impressions and interests regarding 17th Street. Finally, this report reviews future development scenarios of 17th Street that allow 17th Street to be a contributor with a distinctive character to the university. When Kansas State University was transferred from old Bluemont Central College to its current location in 1875, 17th Street, which now crosses the middle of the campus on a North-South axis, was outside of the campus’ core facility areas. As various university programs have grown throughout the late 20th Century, the campus of Kansas State University has expanded toward the west. As a result, the relative proximity of 17th Street to the center of campus has changed. Now, 17th Street is recognized as one of the major entrances to campus from the south; yet because of the street’s initial and ongoing service function and its service-related facilities, there are parts of the corridor that are not attractive. It is desired for 17th Street to become a more appealing and functional part of the university experience for guiding and welcoming visitors to the campus.
Keywords: 17th Street; Kansas State University; Historical look; Manhattan, KS; Regional and community planning; Campus planning; Urban and Regional Planning (0999)